Purification of laboratory chemicals - Armarego, W. L. F.; Chai, Christina Li Lin. (Amsterdam ; Boston : Butterworth-Heinemann, 2003)
Now in its fifth edition, the book has been updated to include more detailed descriptions of new or more commonly used techniques since the last edition as well as remove those that are no longer used, procedures which have been developed recently, ionization constants (pKa values) and also more detail about the trivial names of compounds. In addition to having two general chapters on purification procedures, this book provides details of the physical properties and purification procedures, taken from literature, of a very extensive number of organic, inorganic and biochemical compounds which are commercially available. This is the only complete source that covers the purification of laboratory chemicals that are commercially available in this manner and format. * Complete update of this valuable, well-known reference * Provides purification procedures of commercially available chemicals and biochemicals * Includes an extremely useful compilation of ionisation constants.
Common Physical Techniques Used in Purification; Chemical Methods Used in Purification; Purification of Organic Compounds; Purification of Inorganic and Metal-Organic Compounds; Purification of Biochemicals and Related Products.
Includes indexes.
Includes bibliographical references and index.
Keywords: Chemicals -- Purification; Electronic books